2014
DOI: 10.1038/srep06713
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Analysis of Rat Periaqueductal Gray-Dorsal Horn Reveals Time-, Region- and Frequency-Specific mRNA Expression Changes in Response to Electroacupuncture Stimulation

Abstract: Electroacupuncture (EA) has been widely applied for illness prevention, treatment or rehabilitation in the clinic, especially for pain management. However, the molecular events that induce these changes remain largely uncharacterized. The periaqueductal gray (PAG) and the spinal dorsal horn (DH) have been verified as two critical regions in the response to EA stimulation in EA analgesia. In this study, a genetic screen was conducted to delineate the gene expression profile in the PAG-DH regions of rats to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Effect of EA on physiological pain responses is a basis for understanding EA-induced analgesia. Ke et al [ 39 ] explored some probable EAA-related DEGs in rat PAGs and spinal cords under the physiological condition with cDNA microarray hybridization. However, this method with cDNA microarray hybridization and pooled RNAs only discovered limited information compared with high throughput screening and RNAs from individual samples.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of EA on physiological pain responses is a basis for understanding EA-induced analgesia. Ke et al [ 39 ] explored some probable EAA-related DEGs in rat PAGs and spinal cords under the physiological condition with cDNA microarray hybridization. However, this method with cDNA microarray hybridization and pooled RNAs only discovered limited information compared with high throughput screening and RNAs from individual samples.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 40 ] used EA to stimulate bilateral Zusanli and Kunlun acupoints in rabbits and found that better analgesia was induced by 2 Hz, followed by 30 Hz > 60 Hz > 100 Hz. Wang et al [ 41 ] reported that 100 Hz EA at bilateral Zusanli and Sanyinjiao acupoints induced more effective analgesia than 2 Hz in rats. Cao et al [ 42 ] reported that 15 Hz EA at bilateral Yanglingquan acupoints induced more effective analgesia than 100 Hz EA in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiles of specific organs or tissues after EA stimulation at ST36 have also been analyzed. For example, gene expression profiles in periaqueductal gray-spinal dorsal horn region of rats after EA stimulation at ST36 and SP6 show that the modulation of neural-immune interaction in the central nervous system plays an important role during EA analgesia [ 22 ]. Gene expression profiling of rat arcuate nucleus region responsive to EA at ST36 and SP6 shows that the expression levels of genes are effectively regulated by low-frequency EA, compared with high-frequency EA.…”
Section: Discussionmentioning
confidence: 99%